Gender differences in the perceived impact that athlete leaders have on team member emotional states - Cotterill, S. T.; Clarkson, B. G.; Fransen, K. (Journal of Sports Sciences, 2020)
Emotional contagion has been recognized as a variable influencing individual behaviour and team functioning. In particular, leaders within the team have been suggested to have a significant impact on their teammates through the expression of their emotions. As a result, the aim of this study was to provide greater insight into how different athlete leaders impact the emotional state of their team members, and whether gender differences existed in these relationships. Participants were 295 university student-athletes (200 male and 95 female) recruited from four universities in the UK. Data were collected in a two-step process. First, a voting/rating procedure was conducted within team to identify dominant task, motivational, social and external leaders. Then, participants completed the emotional contagion subscale of the Measure of Empathetic Tendency to rate the impact different athlete leaders had upon their emotional state. A MANOVA was conducted to explore gender differences in reported emotional susceptibility by leadership role. Subsequent ANOVAs highlighted significant differences between leadership role scores for female participants only. The results suggest that female athletes are more susceptible to emotional influence than male athletes. Furthermore, female athletes experienced a greater variation in the perceived emotional influence of different leadership roles in the team.